(3GdHjGf aj abg GdTGaYjIs - (3jMji Hf SGde Hf CSYO Hf jMji, CHh GdMSjf GdYeQGfj,J (B558 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA cJGH GdELGQI bhdg (B: (3aQY (B: (3hgd jLhR ESJFLGQ GdcdGH GdeYdeI ? ajg hLgGf bGd jLhR , dCf efaYgG eHGMI s
(3BNQgG (B:s
(3jfJgi CKfGA cJGH GdfcGM bhdg (B: (3hLejYg ai ebGHdI GdUOGb , hEfeG SdeJ HYVg s
(3GdfSNI HgG MhGTs
(3LRA efgs
(3eged GdfbW CMjGfkGs
(3cJHJ GdYfGhjf HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdTGaYjs